Analysis and Performance Of Grid Connected Straight Driven Pmsg Based Wind Turbines - et. al., Eswaraiah G, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Permanent-magnet synchronous generator (PMSG) are used widely in wind turbine applications. The performance analysis of PMSG can be enhanced by adopting a number of control mechanisms with the benefit of advanced optimization techniques. Renewable energy is harnessed from continuously replenishing natural processes. Some commonly known are sunlight, water, wind, tides, geothermal heat and various forms of biomass. The focus on renewable energy has over the past few decades intensified greatly. This paper presents modeling and control strategy for the grid connected wind turbine system based on Permanent Magnet Synchronous Generator (PMSG). The considered system is based on back-to-back converter topology. The Grid Side Converter (GSC) achieves the DC bus voltage control and unity power factor. The Machine Side Converter (MSC) assures the PMSG speed control. The PMSG is used as a variable speed generator and connected directly to the turbine without gearbox. The pitch angle control is not either considered in this study. Further, Optimal Tip Speed Ratio based MPPT control strategy is used to ensure the most energy efficiency whatever the wind speed variations. A filter (L) is put between the GSC and the grid to reduce current ripple and to improve the injected power quality.During grid faults, a hierarchical coordinated control scheme for the generator-side converter, main grid-side converter and auxiliary grid-side converter, depending on the grid voltage sags, is presented to enhance the low voltage ride through (LVRT) capability of the direct-driven PMSG WT.